EI24 Suppresses Tumorigenesis in Pancreatic Cancer via Regulating c-Myc - Yi Zang; Lei Zhu; Tong Li; Qi Wang; Juanjuan Li; Yuting Qian; Lumin Wei; Mingping Xie; Wen-Hao Tang; Xu Liu; Ying Zhu; Lifu Wang (Gastroenterology Research and Practice)
The EI24 autophagy-associated transmembrane protein is frequently associated with tumor growth and patient survival. In the present study, we found that EI24 was downregulated in pancreatic ductal adenocarcinoma (PDAC) tissues compared with adjacent normal tissues and was associated with cancer cell differentiation. Overexpression of EI24 suppressed cancer cell growth in vitro and in vivo and induced cell cycle S phase arrest, with no impact on caspase-dependent apoptosis. EI24 overexpression also resulted in reduced c-Myc expression, an oncogene in PDAC, accompanied with increased LC3B-II formation, increased Beclin-1, and diminished p62. Together, we propose that EI24 suppresses cell proliferation and prompts cell cycle arrest in pancreatic cancer cells by activating the autophagic lysosomal degradation of c-Myc. Our results suggest a potential mechanism underlying the antitumor effects of EI24 in PDAC and provide insight into the crosstalk between autophagy and cell proliferation involving a possible EI24/Beclin-1/p62/c-Myc signaling pathway.